DEVELOPMENT OF HUMAN RESOURCES WITH MOTIVATIONAL MANAGEMENT TOOLS - G. Shelkoplyasova; A. Kobleva (Вестник Северо-Кавказского федерального университета, 2022)
The article deals with the concept and role of motivational management in the development of human resources of the organization.. The content and structure of motivational management according to scientific concepts are considered. It is proved that the resource capabilities of motivational management are much wider than the standardized system of personnel incentives. The article proves that the ability to individually motivate staff is the primary condition for the development of human resources, in general, the successful management of the organization. The analysis ofresearches is carried out, as a result of which it is established that professional competencies and abilities of employees will bring the desired results to the organization if the manager of the organization is able to apply the tools of motivational management in organizational and managerial activities, taking into account their individual professional and personal needs.